Intestinal Myiasis Caused by Sarcophaga spp. in Cusco, Peru: A Case Report and Review of the Literature - Priscilla Ly; Adiel Aizenberg; Taylor Martin; Martha Lopez; Miguel Arturo Saldaña; Grant Leslie Hughes; Miguel Mauricio Cabada (Case Reports in Infectious Diseases)
Myiasis is the infestation by dipterous fly larvae in humans and animals. The larvae can infect living or necrotic tissue involving the skin, nasopharynx, genitourinary, and gastrointestinal tracts. The accidental ingestion of eggs causes infection of the intestinal tract. We report a case of intestinal myiasis caused by Sarcophaga spp. larvae in a two-year-old child from Limatambo province in the Cusco region of Peru. Live larvae were identified incidentally in this child’s stool sample during the study screening for Strongyloides stercoralis. The child did not have any constitutional or abdominal symptoms. The morphological examination of the specimen under magnification revealed Sarcophaga spp. larvae. We performed a literature review of publications reporting intestinal myiasis caused by Sarcophaga spp. and discussed key aspects of this infestation.